Human parechovirus meningitis in children: state of the art - Elena Bozzola; Sarah Barni; Chiara Barone; Carlo Federico Perno; Andrea Maggioni; Alberto Villani (BMC, 2023)
Abstract Human Parechovirus is a common cause of infection occurring especially during the first years of life. It may present with a broad spectrum of manifestations, ranging from a pauci-symptomatic infection to a sepsis-like or central nervous system disease. Aim of this study is to explore the knowledge on Parechovirus meningitis. According to the purpose of the study, a systematic review of the literature focusing on reports on central nervous system. Parechovirus infection of children was performed following PRISMA criteria. Out of the search, 304 papers were identified and 81 records were included in the revision dealing with epidemiology, clinical manifestations, laboratory findings, imaging, therapy and outcome. Parechovirus meningitis incidence may vary all over the world and outbreaks may occur. Fever is the most common symptom, followed by other non-specific signs and symptoms including irritability, poor feeding, skin rash or seizures. Although several reports describe favourable short-term neurodevelopmental outcomes at discharge after Parechovirus central nervous system infection, a specific follow up and the awareness on the risk of sequelae should be underlined in relation to the reported negative outcome. Evidence seems to suggest a correlation between magnetic imaging resonance alteration and a poor outcome.